Response of People in Tanah Papua in Assessing Special Autonomy as a Challenge and Achievement - Anton Keliat; Hardi Warsono; Kismartini Kismartini (Universitas Medan Area, 2021)
This article aims to analyze the response of the people in Tanah Papua regarding Special Autonomy. Special autonomy in Papua both in Papua Province and West Papua Province is part of the realization of the 1945 constitution and Pancasila. Whereas with equitable justice and the level of welfare of the people in Indonesia, it must become a shared responsibility, both from the central government to the regional governments. The problem was focused on the influence of Special Autonomy in the land of Papua which had an impact on conflict and its development towards improving the welfare of the people in Papua through the responses of the people in assessing this special autonomy. In order to approach this problem, the theory of implementation of public policy by Abdul Wahab Solichin was used. The data were collected through a literature method or approach and were analyzed qualitatively. This study concludes that with the response from the people in Tanah Papua, it will make this Special Autonomy better with autocritics from every element of Papuan society with an appropriate implementation pattern so that it has an impact on the level of prosperity and quality of the indigenous Papuan people.